Pengaruh Edukasi Menggunakan Pocket Book Terhadap Peningkatan Pengetahuan Tentang ISPA Di Kelurahan Pangkalan Dodek Baru - Nurhayati; Suraya, Rani; Rahma Dilla, Nur Indah; Ramadhanu, Suhada; Atifah, Nur (Yayasan Jompa Research and Development, 2025)
Acute Respiratory Tract Infection (ARI) remains a significant public health problem in Indonesia, especially among vulnerable groups such as toddlers and the elderly. Low public knowledge about ARI prevention is a risk factor contributing to the high morbidity rate. This study aims to determine the effect of education using pocket books on increasing public knowledge about ARI in Pangkalan Dodek Baru Village, Batu Bara Regency. The study used a pre-experimental design with a pre-test and post-test approach on 58 respondents selected using an accidental sampling technique. The research instrument was a validated closed-ended questionnaire, and data analysis was conducted using the Wilcoxon test. The results showed that before the intervention, 63.8% of respondents had good knowledge, 20.6% had sufficient knowledge, and 15.6% had insufficient knowledge. After the intervention, all respondents (100%) had good knowledge. The average pre-test score was 7.66, increasing to 9.88 in the post-test, with the Wilcoxon test yielding a p-value of 0.000 (<0.05). Thus, it can be concluded that education using pocket books has a significant impact on increasing public knowledge about ARI. This simple educational medium can be used as an alternative promotional and preventive strategy in efforts to control ARI in the community.